Land Governance in South Africa - Urban LandMark (World Bank, Washington, DC, 2017)
The land governance assessment framework (LGAF) is an innovative and participatory diagnostic tool that assesses the state of land governance in a country. The LGAF has optional modules for other topics such as large-scale land acquisition, forest land, and regularization of rights in urban areas. In South Africa, large-scale land acquisition was selected as an additional thematic area, as was the case in Nigeria. A framework of approximately 21 land governance indicators guides the process in these thematic areas, each divided into three or four dimensions. In South Africa the LGAF process began in 2011. It was started by the World Bank and implemented by urban landmark. This booklet summarizes the results of the LGAF process in South Africa. Section one gives introduction. Section two contextualizes key issues around land, looking at the history, situation today, and the cadastral system. Section three provides a broad overview of where South Africa is doing well, and where not so well, in terms of land governance issues. Sections 4A to 4F present the LGAF findings for each of the six thematic areas, each starting with performance against the LGAF scorecard for that thematic area, and then discussing key issues. Section five summarizes the findings and main recommendations which emerged during the LGAF process in South Africa. Section six concludes this resource, and suggests some key areas for further examination.